Transcendence of Character Values in the Makan Bajambau Tradition in the Kampar Community - Antosa, Zariul; Guslinda, Guslinda; Ananda, Suci; Yona, Yona (Proceedings of the UR International Conference on Educational Sciences, 2018)
The study aims to describe the hidden character values in the ritual tradition of makan bajambau Kampar people in Riau province.Implemented in kampar, Jawi-jawi and Pulau village. This study uses descriptive qualitative research methods. Makan bajambau is a tradition of eating together that is done in welcoming the holy month of Ramadan or completing the sixth fasting month of Syawal. The tradition of makan bajambau is a series of ritual activities performed as a gesture of gratitude for the fasting of Ramadan. Based on the fact that research makan bajambau is a series of joint eating ritual activities carried out by the entire community. The results of the research data analysis can reveal the 9 characters found in makan bajambau culture, namely: religious, disciplined and independent, polite, caring, mutual cooperation, self-confidence, fair, humble and tolerant. Character is that the activity implicitly contains character values. The character value is immersed in the activity of forming the committee, cleaning the grave, and eating together.